2008
DOI: 10.2165/00002018-200831040-00008
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Events Associated with Atomoxetine Treatment for??Attention-Deficit??Hyperactivity Disorder

Abstract: Since the launch of atomoxetine therapy, three spontaneously reported cases of reversible drug-induced liver injury were deemed probably related to it. Atomoxetine should be discontinued in patients with jaundice or laboratory evidence of liver injury and should not be restarted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 16 publications
2
34
0
2
Order By: Relevance
“…We found four studies and two case reports that reported hepatic effects [18,30,[48][49][50][51][52]. The results are compatible with the rarity of reports of liver injury highlighted in the European SPC.…”
Section: Findings In the Predefined Literature Searchsupporting
confidence: 85%
See 3 more Smart Citations
“…We found four studies and two case reports that reported hepatic effects [18,30,[48][49][50][51][52]. The results are compatible with the rarity of reports of liver injury highlighted in the European SPC.…”
Section: Findings In the Predefined Literature Searchsupporting
confidence: 85%
“…The other two studies used Eli Lilly's databases containing spontaneous AEs and clinical trial data to investigate hepatic effects [30,48]. Bangs et al [48] analyzed hepatic-related events in both of these databases, and included clinical trials with short durations (up to 6 months), while Donnelly et al [30] analyzed data from long-term clinical trials (C3 years).…”
Section: Findings In the Predefined Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent summary of clinical trial data from nearly 8000 pediatric and adult patients treated with ATMX found that increases in liver function tests are rare events (Bangs et al 2008). Albeit limited by a small sample size of short duration, adjunct MPH did not alter liver function testing.…”
Section: Hammerness Et Almentioning
confidence: 99%